Isolation and enumeration of bacteria responsible for nosocomial infections from houseflies and determining their susceptibility to poison bait - azam haeidari; DAVOOD KESHAVARZI; Parviz Owlia; Hassan Vatandoost; ATIYEH RAFINEJAD; Rafinejad Javad (Smujo International, 2021)
Abstract. Haeidari A, Keshavarzi D, Owlia P, Vatandoost H, Rafinejad A, Rafinejad J. 2021. Isolation and enumeration of bacteria responsible for nosocomial infections from houseflies and determining their susceptibility to poison bait. Nusantara Bioscience 13: 24-28. Nosocomial infections represent a serious public health concern in developing countries. Houseflies are one of the most common household pests carrying different pathogenic organisms. The purpose of this study was to isolate and enumerate bacteria species from house flies and to determine their susceptibility to Agita® fly bait. Flies were collected from two hospital environments between July to December 2014, in Yazd Province of Iran. Bacterial species were isolated from the outer surfaces of flies, and Agita® efficacy was evaluated based on lethal time (LT50) after 1, 2, 4, 8, 16, and 32 minutes. Three species of bacteria (Escherichia coli, Pseudomonas aeruginosa, and Staphylococcus aureus) responsible for nosocomial infections have been isolated and enumerated from flies. Among the 30 flies collected, 17, 24, and 3 flies were contaminated with E. coli, S. aureus, and Ps. aeruginosa, respectively. The minimum number of isolated bacteria was 3 × 102 CFU/mL, whereas the highest number was 2.4 × 105 CFU/mL. The susceptibility results showed that, despite the existence of a significant effect for heterogeneity in both field and laboratory strains (p-value ? 0/05) and an increase in the mortality of houseflies during the time, there was no significant difference between two strains regarding the efficacy of Agita® against houseflies. The findings of the present study revealed and confirmed that houseflies have an important role in the spread of nosocomial infections in hospital environments, and they are susceptible to Agita® fly bait.